Delegates to the congress waiting in front of the Bolshoy-theatre. Lenin and Sverdlov in the first row, Artem between the 2nd and 3rd column with cap - Ocup, P.A.
Delegates to the congress waiting in front of the Bolshoy-theatre. Lenin and Sverdlov in the first row, Artem between the 2nd and 3rd column with cap.